Tracing the Islamic Journey in Barus: The Genesis of Islam’s Spread - Aisyi, Rahadatul; Hussada, Haria; Pama, Violeta Inayah; Pama, Rumi Magistra (LANGGAM: International Journal of Social Science Education, Art and Culture, 2025)
This article aims to trace Barus as the zero point of the spread of Islam in Indonesia. The study is motivated by Barus’ historical position as an ancient city and a major port on the west coast of Sumatra, which has been identified as the entry point of Islam into the archipelago since the 7th century AD. Using a qualitative approach through field studies and literature review, the findings show that Barus played a significant role in the arrival of Islam through interactions between Muslim traders from Arabia, Persia, and India with local communities, especially via marriage and social assimilation. This interaction gave birth to an early Muslim community that lived harmoniously and left archaeological traces such as the Papan Tinggi and Mahligai tomb complexes, indicating the early presence of Muslims. Thus, Barus not only served as a geographical gateway but also as a center of early Islamic civilization integrated with local culture. The Indonesian government formally recognized Barus’ role by inaugurating the Barus Monument as the “Zero Point of Islam in the Archipelago” on March 24, 2017. This study contributes to a deeper understanding of the historical roots of Islam in Indonesia and highlights the importance of Barus as a cultural heritage site. It suggests the need for further archaeological and historical research in Barus to uncover more evidence about the Islamic civilization in the region. In addition, the findings support the incorporation of Barus into national education curricula and cultural tourism programs to strengthen historical awareness and interreligious harmony.